Clinical outcomes associated with evolving treatment modalities and radiation techniques for base‐of‐tongue carcinoma: thirty years of institutional experience. (26th January 2015) - Chen, Leechuan Andy; Anker, Christopher J.; Hunt, Jason P.; Buchmann, Luke O.; Grossmann, Kenneth F.; Boucher, Kenneth; Fang, Li‐Ming Christine; Shrieve, Dennis C.; Hitchcock, Ying J.
Abstract Curative treatment for base‐of‐tongue squamous cell carcinoma (BOT SCC) has evolved over time; however, comparative outcomes analysis for various treatment strategies is lacking. The authors reviewed the evolution of treatment modality and radiotherapy (RT) technique for 231 consecutive BOT SCC patients at our institution between 1981 and 2011. Treatment modalities included definitive chemoradiotherapy (chemoRT) (42%), definitive RT (33%), surgery followed by RT (20%), and surgery alone (5%). RT techniques included external beam plus interstitial brachytherapy (EBRT + IB) (37%), conventional EBRT (29%), intensity‐modulated radiation therapy ± simultaneous integrated boost (IMRT ± SIB) (34%). Clinical characteristics and outcomes were stratified by modality or RT technique. Treatment modality evolved from definitive RT (1980s–1990s) to definitive chemoRT (1990s–2000s). RT technique evolved from EBRT + IB (1980s–1990s) to conventional EBRT (1990s–2000s) to IMRT + SIB (2000s). With median alive follow‐up of 6 years (0.3–28 years), the 5‐year LC, LRC, and OS rates were 80%, 73%, and 51%. There was no difference in distribution of gender, age, stage among treatment modalities. Definitive chemoRT had improved LRC (HR 1.6) and OS (HR 1.7) compared to definitive RT. IMRT + SIB had improved LRC (HR 3.2), DFS (HR 3.4), and OS (HR 3.0) compared to conventional EBRT. Over the past 30 years, BOT SCC treatment has undergone major paradigm shifts that incorporate nonsurgical functional preservation, concurrent chemotherapy, and advanced RT techniques. Excellent locoregional control and survival outcomes are associated with accelerated IMRT with chemotherapy.